Periodische und aperiodische Wasserstandsschwankungen des Laacher Sees - Henning, Ingrid (ERDKUNDE, 1967)
As a contribution to the hydrology of the Eifel lakes, the records of the water-level gauge on the Laacher See were examined. At the time of summer stagnation, oscillations occur with the periodicity of the internal wave movement (Seiches). Until now, internal wave movement could only be determined by temperature registration inside stratified water masses. Direct observations on a lake surface were made for the first time on the Laacher See. The aperiodic water-level variations how unusually high reserves in the lake basin and show also the extreme relationships of the hydrologic years 1965 and 1966. The connections between lake water-levels and precipitation are presented, and show that the Laacher See receives all its water from precipitation. The mean annual precipitation at the Maria Laach monastery for the period 1930-1959 was 653 mm. These water receipts are sufficient to cover discharge and evapotranspiration. Thus the theories which claim additional groundwater supplies from an area outside the surface watershed or from juvenile water are refuted.